2006
DOI: 10.1038/sj.jcbfm.9600290
|View full text |Cite
|
Sign up to set email alerts
|

D-Amphetamine Stimulates D2Dopamine Receptor-Mediated Brain Signaling Involving Arachidonic Acid in Unanesthetized Rats

Abstract: In rat brain, dopaminergic D 2 -like but not D 1 -like receptors can be coupled to phospholipase A 2 (PLA 2 ) activation, to release the second messenger, arachidonic acid (AA, 20:4n-6), from membrane phospholipids. In this study, we hypothesized that D-amphetamine, a dopamine-releasing agent, could initiate such AA signaling. The incorporation coefficient, k* (brain radioactivity/integrated plasma radioactivity) for AA, a marker of the signal, was determined in 62 brain regions of unanesthetized rats that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 95 publications
(147 reference statements)
5
22
0
Order By: Relevance
“…The fact that effects were only seen at the highest fat concentration in the intermittent groups suggests that both the manner and amount of fat consumed may influence actions within regions of the brain relevant to reward. For instance, fat intake, either total amount over time or large bolus amounts, may alter D2 actions via changes in arachidonic acid-dependent signal transduction and/or the formation of lipid rafts (Bhattacharjee, et al, 2005(Bhattacharjee, et al, , 2006Jacobowitz and Kallarakal, 2004).…”
Section: Raclopride: Dopamine D 2 -Like Antagonistmentioning
confidence: 99%
“…The fact that effects were only seen at the highest fat concentration in the intermittent groups suggests that both the manner and amount of fat consumed may influence actions within regions of the brain relevant to reward. For instance, fat intake, either total amount over time or large bolus amounts, may alter D2 actions via changes in arachidonic acid-dependent signal transduction and/or the formation of lipid rafts (Bhattacharjee, et al, 2005(Bhattacharjee, et al, , 2006Jacobowitz and Kallarakal, 2004).…”
Section: Raclopride: Dopamine D 2 -Like Antagonistmentioning
confidence: 99%
“…In control animals fed a LiCl-free diet, quinpirole-induced increases in k* are robust and widespread in brain regions within dopaminergic circuits, and can be blocked by pre-treatment with the D 2 -like receptor antagonists, butaclamol or raclopride [16,29]. In addition to LiCl, chronic CBZ has been reported to attenuate dopamine function in rats, suggesting that normalization of a dysfunctional dopamine neurotransmission may underlie CBZ effects in bipolar disorder [2,4,35,38].…”
Section: Introductionmentioning
confidence: 99%
“…With it, we showed in unlesioned unanesthetized rats that acute administration of quinpirole, a D 2 -receptor agonist, increased k* for AA in brain regions with high densities of D 2 -receptors, and that the increases could be blocked by the preferential D 2 -receptor antagonist, butaclamol (Bhattacharjee et al, 2005;Bristow et al, 1998;Hayakawa et al, 2001). We also reported that D-amphetamine, which increases synaptic DA by increasing presynaptic DA release and reducing DA reuptake by the DAT, increased k* for AA in a dosedependent manner in brain areas rich in D 2 -receptors (Bhattacharjee et al, 2006). Damphetamine's effects could be prevented entirely by pre-administration of raclopride, a selective D 2 -receptor antagonist (Bhattacharjee et al, 2006;Kohler et al, 1985), indicating that they were mediated specifically by D 2 -receptors.…”
Section: Introductionmentioning
confidence: 75%
“…We also reported that D-amphetamine, which increases synaptic DA by increasing presynaptic DA release and reducing DA reuptake by the DAT, increased k* for AA in a dosedependent manner in brain areas rich in D 2 -receptors (Bhattacharjee et al, 2006). Damphetamine's effects could be prevented entirely by pre-administration of raclopride, a selective D 2 -receptor antagonist (Bhattacharjee et al, 2006;Kohler et al, 1985), indicating that they were mediated specifically by D 2 -receptors.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation